2013
DOI: 10.1007/s12272-013-0295-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and pattern recognition analyses of magnoflorine, spinosin, 6′′′-feruloyl spinosin and jujuboside A by HPLC in Zizyphi Semen

Abstract: Two rapid and simple HPLC methods with UV detector to determine three main compounds (magnoflorine, spinosin and 6′′′-feruloyl spinosin) and evaporative light scattering detector (ELSD) to determine jujuboside A were developed for the chemical analyses of Zizyphi Semen. Magnoflorine, spinosin, and 6′′′-feruloyl spinosin were separated with an YMC J’sphere ODS-H80 column (250 mm × 4.6 mm, 4 μm) by the gradient elution followed by the isocratic elution using methanol with 0.1 % formic acid and water with 0.1 % f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It can be seen that a few standards and methods have been reported to evaluate the quality of SZS preparations, which are mostly focused on analysis of certain type of chemicals based on HPLC, UV or TLCS, etc [6], [7], [8]. Reported studies have displayed quantitative determination for three main types of active components, namely, saponins, flavonoids and triterpenoids in SZS using an alcohol-water mixture, [9], [10], [11]. It is generally accepted that most of traditional Chinese medicines generate medical effect by the synergic action of a variety of chemical components.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that a few standards and methods have been reported to evaluate the quality of SZS preparations, which are mostly focused on analysis of certain type of chemicals based on HPLC, UV or TLCS, etc [6], [7], [8]. Reported studies have displayed quantitative determination for three main types of active components, namely, saponins, flavonoids and triterpenoids in SZS using an alcohol-water mixture, [9], [10], [11]. It is generally accepted that most of traditional Chinese medicines generate medical effect by the synergic action of a variety of chemical components.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported in some previous studies that the six components analyzed in this study were active components which exerted sedative-hypnotic effect [ 3 8 ]. Using the UHPLC-QQQ-MS/MS method developed in this experiment, the six components with different types of structures could be well separated and quantified within 6 minutes.…”
Section: Resultsmentioning
confidence: 87%
“…There are many different categories of chemical constituents in ZSS, including flavonoids, saponins, and triterpenoids. Spinosin, jujuboside A, and jujuboside B were reported to be active components which exerted sedative-hypnotic effect [ 3 8 ]. It was found that the sedative-hypnotic effect of ZSS might be due to the action of its chemical constitutions, such as spinosin, jujuboside A, and jujuboside B, on serotonergic system and GABA receptors [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other saponin types include ursane, dammarane, lupane or epiceanothane (Yang et al ., ). Flavonoids consist of swertisin, spinosin (2″‐β‐O‐glucopyranosyl swertisin, a C‐glycoside flavonoid, about 0.1% weight [(Kim et al ., )]), 6″′‐feruloyl spinosin, siospinosin, 6″′sinapoylspinosin, apigenin‐6‐C‐β‐D‐Glu, isovitexin‐2″‐O‐β‐D‐Glu and puerarin (Cheng et al ., ), epigallocatechin and gallocatechin (Kadioglu et al ., ). Cyclopeptide alkaloids include amphibine D, sanjoinine A, B, C (Han et al ., ), and K and zizyphusine (Li et al ., 2007) steroids.…”
Section: Ziziphus Jujuba Seeds (Table  and Fig )mentioning
confidence: 99%